2012
DOI: 10.1111/j.1365-2125.2012.04334.x
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1, randomized, placebo‐controlled, dose‐escalation study of an anti‐IL‐13 monoclonal antibody in healthy subjects and mild asthmatics

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• IL-13 can recapitulate the key pathological and clinical features of asthma.• Exhaled NO (FeNO) concentrations are elevated under conditions of pulmonary inflammation, including asthma.• Therapies that inhibit signalling by both IL-13 and the functionally redundant cytokine IL-4 have demonstrated reductions in FeNO, although relationship to dose was not reported. WHAT THIS STUDY ADDS• This study provides the first report of the safety and pharmacokinetics of GSK679586,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 36 publications
(37 reference statements)
0
33
0
Order By: Relevance
“…GSK679586 increased serum total IL-13 and reduced FeNO in 28 mild intermittent asthmatics versus placebo [170]. In a subsequent 12 week trial in 198 severe asthmatics who remained uncontrolled (ACQ7 P 1.5) despite being up-titrated to maximal doses of ICS (P1000 lg fluticasone per day), plus or minus LABA and OCS, GSK679586 was dosed intravenously at 10 mg/kg monthly.…”
Section: Clinical Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…GSK679586 increased serum total IL-13 and reduced FeNO in 28 mild intermittent asthmatics versus placebo [170]. In a subsequent 12 week trial in 198 severe asthmatics who remained uncontrolled (ACQ7 P 1.5) despite being up-titrated to maximal doses of ICS (P1000 lg fluticasone per day), plus or minus LABA and OCS, GSK679586 was dosed intravenously at 10 mg/kg monthly.…”
Section: Clinical Experiencementioning
confidence: 99%
“…GSK's mAb GSK679586 (M1) is a humanized IgG1 with an affinity (K D ) for IL-13 of 300-400 pM [170]. GSK679586 increased serum total IL-13 and reduced FeNO in 28 mild intermittent asthmatics versus placebo [170].…”
Section: Clinical Experiencementioning
confidence: 99%
“…Although eosinophils express the IL-13 receptor, 85 the clinically beneficial effects of antagonizing IL-13 in vivo are more likely to be due to its effects on other cells, thereby secondarily improving eosinophilic inflammation. Several monoclonal antibodies that specifically block IL-13 biology are in clinical trials for either asthma, ulcerative colitis or EoE and include lebrikizumab, 8688 anrukinzumab, 89 tralokinumab, 9092 GSK679586 93, 94 and RPC4046 (https://clinicaltrials.gov/ct2/show/NCT02098473). However, by targeting IL-4Rα1 instead, blockade of both IL-4 and IL-13 biology can be achieved, as was explored with monoclonal antibody AMG 317 in asthma 95 and so far, more successfully in atopic dermatitis and asthma with dupilumab.…”
Section: Novel Therapies That May Indirectly Affect Eosinophils That mentioning
confidence: 99%
“…The selected maximum dose (10.0 mg/kg, IV) for FIH study of CNTO 5825 provided predicted systemic exposures that were below observed systemic exposures at NO-AEL in rats and cynomolgus monkeys. In addition, the selected doses (0.1, 0.3, 1.0, 3.0 and 10.0 mg/kg) of CNTO 5825 for FIH study were within the range of doses that have been evaluated in clinical studies of related anti-IL-13 mAbs [33][34][35][36].…”
Section: Discussionmentioning
confidence: 94%